Optimized Extraction of Total Phenolic Compounds from Nelumbo nucifera Gaertn Using Microwave Assisted Extraction (MAE) - นาคประสม, กาญจนา; วาฤทธิ์, จตุรภัทร; อุประ, อุมาพร; ทนงการกิจ, หยาดฝน; นาคประสม, นักรบ (KKU Science Journal, 2017)
The objectives of this research was to study the conditions that optimize the extraction of total phenolic compounds from Nelumbo Nucifera Gaertn petals using microwave assisted extraction (MAE) and also investigated their antioxidant activities of the crude extracts. Variables used to study the optimal extraction conditions of total phenolic compounds include concentration of ethanol (10-50 %v/v), extraction time (10-20 min) and microwave power (200-400 watts). Furthermore, the optimal combination of these variables were determined using a response surface methodology (RSM) by Box Behnken design. The results showed that these three factors affected yield of extracted total phenolic. Moreover, the statistical analysis provided indications that the data obtained from the experiment should be fitted to polynomial equation because of its high coefficient of determination with R-square = 0.9314. The 3D response surface plot and the contour plot derived from the mathematical models were used to determine the optimal conditions for extraction of total phenolic compounds from Nelumbo Nucifera Gaertn petals using MAE. The highest yields of total phenolic compounds were obtain when the samples were dissolved in ethanol at 34%v/v, the extraction time was set at 15 min and the microwave power was set at 300 watts. Under these optimal conditions, the highest total phenolic compounds yield were 134.58±0.20 mgGAE/gDW from experimental values and 134.56 mgGAE/gDW from predicted values and the scavenging activity of percentage of inhibition in DPPH assay was 24.02%.